What works for wellbeing in culture and sport? Report of a DELPHI process to support coproduction and establish principles and parameters of an evidence review. (September 2017) - Daykin, Norma; Mansfield, Louise; Payne, Annette; Kay, Tess; Meads, Catherine; D'Innocenzo, Giorgia; Burnett, Adele; Dolan, Paul; Julier, Guy; Longworth, Louise; Tomlinson, Alan; Testoni, Stefano; et al.
Aims: There is a growing recognition of the ways in which culture and sport can contribute to wellbeing. A strong evidence base is needed to support innovative service development and a 3-year research programme is being undertaken to capture best evidence of wellbeing impacts and outcomes of cultural and sporting activities in order to inform UK policy and practice. This article provides an overview of methods and findings from an initial coproduction process with key stakeholders that sought to explore and agree principles and parameters of the evidence review for culture, sport and wellbeing (CSW). Methods: A two-stage DELPHI process was conducted with a purposeful sample of 57 stakeholders between August and December 2015. Participants were drawn from a range of culture and sport organisations and included commissioners and managers, policy makers, representatives of service delivery organisations (SDOs) and scholars. The DELPHI 1 questionnaire was developed from extensive consultation in July and August 2015. It explored definitions of wellbeing, the role of evidence, quality assessment, and the culture and sport populations, settings and interventions that are most likely to deliver wellbeing outcomes. Following further consultation, the results, presented as a series of ranked statements, were sent back to participants (DELPHI 2), which allowed them to reflect on and, if they wished, express agreement or disagreement with the emerging consensus. Results: A total of 40 stakeholders (70.02%) responded to the DELPHI questionnaires. DELPHI 1 mapped areas of agreement and disagreement, confirmed in DELPHI 2. The exercise drew together the key priorities for the CSW evidence review. Conclusion: The DELPHI process, in combination with face-to-face deliberation, enabled stakeholders to engage in complex discussion and express nuanced priorities while also allowing the group to come to an overall consensus and agree outcomes. The results will inform the CSW evidence review programme until its completion in March 2018.